Can a new emergency response system reduce traffic fatalities? The case of the 911-emergency response system in the Dominican Republic. (August 2020) - Nazif-Munoz, José Ignacio; Puello, Adrián; Williams, Augusta; Nandi, Arijit
Highlights: Studies in low- and middle-income countries focusing on emergency response system (ERS) and traffic fatalities have shown considerable discrepancies. In May 2014, the Dominican Republic introduced the 911-ERS to reduce, among other challenges, traffic mortalities in Santo Domingo. The introduction of the 911-ERS in this city was not associated with important reductions in traffic fatality rates. In the Dominican Republic, the efficacy of the 911-ERS to address the burden of road traffic fatality requires further improvements. Abstract: Background: In May 2014, the Dominican Republic introduced the 911-emergency response system (ERS) in Santo Domingo. Before its introduction, more than 40 phone numbers were available to report emergencies. The objective of this work is to assess whether this new emergency response system was effective in reducing traffic fatalities. Methods: Weekly numbers of traffic fatalities per population and per vehicle fleet from January 2013 to December 2015 were obtained from the Ministry of Health and the National Institute of Statistics. A hybrid time-series difference-in-difference analysis using multivariable negative binomial regression models were used to compare trends in rates of traffic fatalities in Santo Domingo to La Romana and Santiago, before and after the introduction of the 911-ERS. Results: Estimates from negative binomial models suggest that the introduction of the 911-ERS in Santo Domingo relative to Santiago-La Romana was associated with a 17% reduction in the Incidence Rate Ratio (IRR) of traffic fatalities per 1 000 000 population (IRR = 0.83, 95% confidence interval [CI]: 0.67; 1.03) and with a 20% reduction in the IRR of weekly traffic fatalities per 1 000 000 vehicle fleet (IRR = 0.80, 95% CI:0.67; 0.99). Discussion: Our findings suggest that transitioning from multiple to one unique emergency phone number should be considered more attentively. Furthermore, the case of the Dominican Republic calls for more theoretical and methodological research to understand how to assess these road safety policies more accurately. Since various studies suggest that 911-ERS mature in the long run, how these systems evolve over time and other related variables should be carefully considered.